Innovation in Developing Indonesian Language Learning Media Based on Problems to Enhance Critical Thinking Skills of Students in Multi-Ethnic Primary Schools - Rahmadanirwati, Dewi; Zaim, M. (International Education Trend Issues, 2024)
This research aimed to explore the effectiveness of innovation in developing Indonesian language learning media based on problems to enhance the critical thinking skills of elementary school students in multi-ethnic areas. The research method used was an experiment with a pre-test and post-test design on the same subjects, involving one group of students who use problem-based learning media. This research was conducted in South Jakarta, which has a population of students from diverse ethnic backgrounds. The number of respondents was 27 from various ethnic groups. During the research period, data on critical thinking skills were collected through validated assessment instruments, taking into account the multi-ethnic context. Data analysis indicated that students who used problem-based learning media experienced a significant improvement in their critical thinking skills compared to the control group. This improvement was reflected in students' abilities to analyze information, evaluate arguments, and produce vital and reflective thinking in the context of the diverse Indonesian language.